Effect of Probiotics Supplementation on Heart Rate: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Han, Shufen; Li, Yuezhen; Song, Ruijuan; Gao, Hui; Zhang, Weiguo (Frontiers in Nutrition, 2022)
Background and Aims: Probiotics consumption lowers the risk of cardiovascular disease, but whether it affects heart rate (HR) remains controversial. Therefore, our study aimed to assess the chronotropic effects of probiotics on heartbeat via a meta-analysis of randomized clinical trials. Methods: Relevant studies were identified by searching PubMed, Cochrane library, and Clinical Trials databases up to October 2021. Either a fixed-effects or a random-effects model was used to calculate the pooled effect sizes and 95% confidence intervals (CIs). Results: This meta-analysis included 13 studies involving 16 interventional trial arms and 931 participants according to inclusion criteria. The overall pooled estimate showed that probiotics supplementation had a slight, but no significant reduction of 0.28 bpm (95% CI: -1.17, 0.60) on HR. Relatively high heterogeneity was observed among included trials (I2= 80.8%, P heterogeneity < 0.001). Subgroup analysis displayed that probiotics supplementation significantly reduced HR by 2.94 bpm (95% CI: -5.06, -0.82) among participants with baseline HR ≥ 75 bpm, by 1.17 bpm (95% CI: -2.34, -0.00) with probiotics dose ≥ 1×1010 CFU/day, and by 1.43 bpm (95% CI: -2.69, -0.17) with multiple-strain intervention. Meta-regression analysis showed that baseline HR was a major potential effect modifier of probiotics supplementation on lowering HR. Conclusion: Hitherto, the overall evidence in the literature was insufficient to support the notion that probiotics supplementation has a class effect on HR reduction. However, in subgroup analysis, probiotics reduced HR significantly in those who had higher baseline HR, received a higher dose or multiple strains of probiotics.